Genomic Epidemiology of Antimicrobial Resistance: Tracking the Global Spread of Resistant Pathogens - Seelall, Joshua (International Journal of Scientific Research and Management (IJSRM), 2024)
The rapid development and spread of antimicrobial resistance have been one of the most prominent health crises globally, which significantly challenges treating infectious diseases. This paper will address the contribution that genomic epidemiology makes to track and understand the global spread of antimicrobial-resistant pathogens. Genomic epidemiology, an area combining pathogen genomics with epidemiological data, allows for an extremely powerful approach in the identification of resistance mechanisms and tracing transmission routes for guiding public health interventions. This review Emphasizes major bacterial pathogens, such as Escherichia coli, Staphylococcus aureus, and Klebsiella pneumoniae, which harbor major resistance genes: blaCTX-M, mecA, and blaKPC. These genes contribute to the worldwide dissemination of resistance, mainly through mechanisms involving horizontal gene transfer and selective antibiotic pressure. Thus, genomic surveillance, phylogenetic analysis, and bioinformatics approaches allow for the pinpointing of transmission hotspots, mapping of resistance gene distribution, and tracking of emerging resistant strains in real time.It also provides information on how genomic data are being used to improve antimicrobial stewardship programs and inform clinical treatment decisions. Public health responses can further be tailored by recognizing regional resistance patterns, hence enhancing interventions. However, several challenges persist—for example, the need for standardized sharing of data, interpretation of genomic data, and integration of these insights into public health systems, especially in low-resource settings.This abstract highlights the transformative impact of genomic epidemiology in the management of the AMR crisis while emphasizing the continued need for global cooperation, enhanced data infrastructures, and policy initiatives to ensure the effective use of genomic data in public health.